Estimating an Efficient Routing in MANET for UDP and TCP Traffic - Hossen, Md. Repon; Ahmed, Khandaker Takdir; Saha, Sonali; Hossain, Zakir (Discoveries in Agriculture and Food Sciences, 2016)
Mobile computing applications have enjoyed a tremendous improvement and enhancement due to recent technological advances in computers and wireless communication devices. The enormous use of information technology and the demand for mobile communication ‘anywhere, anytime’ has fueled the need for dynamically reconfigurable networks. Mobile ad hoc networks (MANETs) provide continuous network connectivity to mobile computing devices. Performance analysis of routing protocols used for MANETs under varying conditions and constraints is a full of zipping area of research at present. In this paper, we compare UDP and TCP traffic in respect to three MANETs protocols namely AODV, DSR and DSDV. Here we consider a network scenario of fixed nodes and fixed pause time, these nodes are varying with respect to different mobility speed to check the difference between UDP and TCP traffic.